Serum Lipid Profile in Patients With Primary Adrenal Insufficiency Receiving Glucocorticoid Replacement - Marta Fichna; Piotr Fichna; Marta Sumińska; Bolesław Gębarski; Marek Ruchała (Clinical Endocrinology, 2026)
ABSTRACT Objective Glucocorticoid (GC) replacement in Addison's disease (AD) usually fails to mimic physiological circadian cortisol rhythm. Recurrent hypercortisolemia may contribute to central obesity, hyperglycemia and dyslipidemia, which could explain cardiovascular mortality in AD. Steroid excess alters lipid profile, while effects of the replacement doses remain inconsistent, which led us to evaluate serum lipids in AD. Design A cross‐sectional study in patients treated for autoimmune AD. Patients The study comprised 66 patients diagnosed 1 year (AD2) before the study and 96 matched controls (CON), excluding individuals with diabetes, thyroid dysfunction and lipid‐lowering treatment. Measurements Investigations included physical examination and biochemical analyses. Results All patients were on immediate‐release hydrocortisone (HC), mean ± SD 22.7 ± 6.6 mg/day. AD1 presented significantly lower HC dosage ( p ≤ 0.001), higher TSH ( p ≤ 0.046) and lower fasting glucose ( p ≤ 0.005) versus AD2 and CON. Recently treated patients demonstrated significantly lower total cholesterol (TC), LDL‐C and triglyceride (TG) levels versus both AD2 and CON, who displayed similar lipid profile. Only HDL‐C was significantly higher in AD2 ( p = 0.009). Hyperlipidemia was found in 62.5% CON subjects, 45.5% AD1 ( p = 0.032), and 60.8% AD2 patients ( p = 0.811). Age was strongly correlated with TC and LDL‐C in AD and CON. Daily HC dose correlated with TC and LDL‐C in both AD1 and AD2, and with HDL‐C in AD1, and multivariable regression confirmed its predictive value with regard to TC and LDL‐C. Conclusions The risk of hyperlipidemia in patients receiving GC replacement does not seem elevated. Nonetheless, metabolic complications should be screened to improve long‐term outcomes.